Notched Sound Alleviates Tinnitus by Reorganization Emotional Center - Huang, Bixue; Wang, Xianren; Wei, Fanqing; Sun, Qiyang; Sun, Jincangjian; Liang, Yue; Chen, Huiting; Zhuang, Huiwen; Xiong, Guanxia (Frontiers in Human Neuroscience, 2022)
Background: Tinnitus is a common disease among modern people, and sound therapy is an effective method to alleviate it. Previous studies have shown that Notched sound not only changes levels of cortical blood oxygen, but affects blood oxygen in specific cerebral cortical areas, such as Broadmann area 46(BA46), which is associated with emotion. Extensive evidence has confirmed that tinnitus is closely related to emotion. Whether Notched sound plays a role in regulating the emotional center is still unclear. Methods: This study included 29 patients with newly diagnosed chronic tinnitus who were treated with Notched sound. Functional near-infrared spectroscopy (fNIRS) was conducted before and after treatment to observe bilateral changes in cortical blood oxygen in the cerebral hemispheres. We compared the changes in connectivity between the two regions of interest (the superior temporal gyrus and BA46), as wells as other cortical regions before and after treatment. Results: The results showed (1) that global connectivity between the bilateral auditory cortex of the superior temporal sulcus and the ipsilateral cortex did not change significantly between baseline and the completion of treatment, and (2) that the connectivity between channel 14 and the right superior temporal sulcus decreased after treatment. The overall connectivity between the right BA46 region and the right cortex decreased after treatment, and decreases in connectivity after treatment were specifically found for channels 10 and 14 in the right parietal lobe and channels 16, 20, 21, and 22 in the frontal lobe, while there was no significant change on the left side. There were no significant changes in the questionnaire measures of tinnitus, anxiety, or depression before and after treatment. Conclusion: The results of the study indicate that cerebral cortex reorganization occurs in tinnitus patients after receiving treatment with Notched sound for one month, and that Notched sound causes a decrease in the connectivity between the auditory cortex and specific brain regions. Significance: Notched sound not only regulates the auditory center through lateral inhibition, but also alleviates tinnitus by reorganizing the emotional control center.